(untitled) (JED (Jurnal Etika Demokrasi), 2020)
The Regional Representative board of the Republic of Indonesia is one of the state institutions mentioned in the 1945 Constitution of the Republic of Indonesia. Although it has high legitimacy, it is not comparable with its authority. The position of the Indonesian Regional Representative Board (DPD RI) does not have authority in the legislative function, although it is limited to submitting and discussing certain draft laws that have been proposed, as well as in terms of supervision which is limited to supervising the implementation of certain laws and discussing and provide consideration of the results of its supervision to the House of Representatives (DPR). The ideal idea to strengthen the position of the Indonesian Regional Representative Board from experts, as well as from the results of the analysis of the author is carried out the fifth amendment to the 1945 Constitution of the Republic of Indonesia, one of which is in terms of its authority so that it is equal to the authority of the House of Representatives, which can participate in deciding the draft law related to its authority following Article 22D of the 1945 Constitution of the Republic of Indonesia. Besides that, so that the Indonesian legislative body can adopt strong bicameralism, unperfect bicameralism. Keywords: Position Regional Representative board of the Republic of Indonesia Bicameral system, and the rule of law Dewan Perwakilan Daerah Republik Indonesia merupakan salah satu lembaga negara yang disebutkan dalam Undang-Undang Dasar Negara Republik Indonesia Tahun 1945. Meskipun memiliki legitimasi tinggi, namun hal tersebut tidak sebanding dengan kewenangan yang dimilikinya. Kedudukan Dewan Perwakilan Daerah Indonesia (DPD RI) tidak mempunyai wewenang dalam fungsi legislasi, meskipun hanya sebatas mengajukan serta membahas rancangan undang-undang tertentu yang telah diajukan, begitu pun dalam hal pengawasan yang hanya sebatas mengawasi terkait pelaksanaan terhadap undang-undang tertentu dan membahas serta memberikan pertimbangan hasil pengawasannya ke Dewan Perwakilan Rakyat (DPR). Gagasan ideal untuk memperkuat Kedudukan Dewan Perwakilan Daerah Indonesia dari para ahli, maupun dari hasil analisis penulis adalah dilakukan amandemen kelima Undang-Undang Dasar Negara Republik Indonesia Tahun 1945, salah satunya yaitu dari segi kewenangannya agar setara dengan kewenangan Dewan Perwakilan Rakyat, yang dapat ikut memutuskan rancangan undang-undang yang terkait dengan kewenangannya sesuai Pasal 22D Undang-Undang Dasar Negara Republik Indonesia Tahun 1945. Disamping itu juga agar lembaga legislatif Indonesia dapat menganut lembaga perwakilan kuat (strong bicameralism), bukan yang sempurna (perfect bicameralism). Kata kunci: Kedudukan DPD RI, Sistem Bikameral, dan Negara Hukum